Characteristics and Outcomes in Patients Without Prenatal Care With PROM Less Than 34 Weeks of Gestation [14R]. (May 2016) - Patel, Krunal; Williams, Shauna; Apuzzio, Joseph; Bilinski, Robyn T.; Guirguis, George
Abstract : INTRODUCTION: The patients who present to a labor unit with preterm premature rupture of membranes (PPROM) without prenatal care (PNC) may pose significant challenges for providers. The study objective was to compare demographic and delivery outcomes in women with PPROM who had PNC with those without PNC. METHODS: This is a retrospective cohort study of women from January 1, 2001 to December 31, 2014 with a singleton pregnancy with PPROM. Patients were included if the gestational age on admission was 23 0/7 to 33 6/7 weeks. No PNC was defined as having no prior outpatient visits during the pregnancy. Mann-Whitney, Student's t test, Chi-square and Fisher's exact tests were used. RESULTS: 284 patients met inclusion criteria, 65 (22.9%) had no PNC. Gestational age at admission, delivery gestational age and birth weight did not differ between the two groups. Rates of HIV, gonorrhea, chlamydia and trichomonas did not differ. Drug use was higher in the no PNC group (57% vs 16%, P <.0001) as was tobacco use (57% vs 20.5%, P <.0001) and GBS carriage (48% vs 24%, P =.0007). Median latency period was 2 days shorter (no PNC: 3 days; PNC: 5 days, P =.023). Rates of abruption, cesarean delivery, clinical and histologic chorioamnionitis and endometritis did not differ. CONCLUSION: Gestational age at delivery and rates of serious obstetric complications did not differ between the groups. Further research is needed for patients with limited care who reach term as current guidelines for prophylaxis may be insufficient.